KELEBIHAN ASUPAN IODIUM YANG KRONIK PADA IBU MENYUSUI DAN BAYINYA - Djoko Kartono; Sri Supadmi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2013)
ABSTRACTExcess or deficiency of iodine are associated with thyroid disorders such as hyperthyroidism and hypothyroidism. In District of Demak, median urinary iodine concentration (UIC) was very high but still no explanation of the causes on thyroid function of the population. To analyze iodine status of lactating mothers and their infant and sources of iodine. Participants were lactating mothers and their infant <6 months. Data collection included UIC urine spot, thyroid stimulating hormone (TSH) and free thyroxine (fT4) serum of lactating mothers and blood of infants, iodine in breast milk, iodine in salt and drinking water. Median UIC of lactating mothers and infants was 1040 and 1995 μg/L respectively. Neither lactating mothers nor infant had UIC <100 μg/L, however, proportion UIC >500 μg/L was 66.9 percent and 90.8 percent respectively. Median breast milk iodine concentration (BMIC) was 850 μg/L and 4.2 percent had BMIC <120 μg/L. Mean TSH of lactating mothers and infant was 1.49+0.99 and 11.25+3.94 μIU/mL respectively. Proportion TSH <0.3 μIU/mL of lactting mothers was 10.2 percent but none TSH >6.2 μIU/mL. Meanwhile, none of infants had TSH <0.7 μIU/mL but 3.1 percent had TSH >34.0 μIU/mL. Mean fT4 of lactating mothers was 1.04+ 0.26 μmol/L. Proportion of fT4 <0.8 μmol/L was 11.5 percent and none had fT4 >2.0 μmol/L. Mean iodine in household’s salt was 30.0+ 20.8 ppm (range: 7.1-78.3 ppm). Meanwhile, median iodine in drinking water was 650 μg/L (range: 50-1791 μg/L). Iodine intake of lactating mothers and their infant, from drinking water, was very high. Among lactating mothers, there was a risk of subclinical hyperthyroidism as well as overt hyperthyroidism. In contrary, there was a risk of hypothyroidism of infants <6 months of age.Key words: excess iodine, iodine status, lactating mothers, infant, salt, waterABSTRAKKelebihan dan kekurangan iodium berhubungan dengan gangguan tiroid seperti hipertiroidisme dan hipotiroidisme. Di Kabupaten Demak, median ekskresi iodium urin (EIU) sangat tinggi namun belum ada informasi tentang gangguan tiroid penduduknya. Melakukan analisis status iodium ibu menyusui dan bayinya dan sumber utama iodium. Sampel adalah ibu menyusui dan bayi umur <6 bulan. Data yang dikumpulkan meliputi EIU dari urin sesaat, thyroid stimulating hormone (TSH) dan free thyroxine (fT4) serum ibu menyusui dan darah bayi, iodium air susu ibu (ASI), iodium garam dan air minum. Median EIU ibu menyusui dan bayi adalah 1040 dan 1995 μg/L. Tidak ada ibu menyusui maupun bayi mempunyai EIU <100 μg/L, namun, proporsi EIU >500 μg/L adalah 66,9 persen dan 90,8 persen. Median kadar iodium ASI adalah 850 μg/L dan sebanyak 4,2 persen mempunyi iodium ASI <120 μg/L. Rata-rata TSH ibu menyusui dan bayi adalah 1,49+0,99 dan 11,25+3,94 μIU/mL. Proporsi TSH <0,3 μIU/mL ibu menyusui adalah 10,2 persen tapi tidak ada TSH>6,2 μIU/mL. Sementara itu, tidak ada bayi mempunyai TSH <0,7 μIU/mL tetapi 3,1 persen mempunyai TSH >34,0 μIU/mL. Rata-rata fT4 ibu menyusui adalah 1,04+0,26 μmol/L. Proporsi fT4 <0,8 μmol/L adalah 11,5 persen dan tidak ada yang mempunyai fT4 > 2,0 μmol/L. Rata-rata iodium garam rumah tangga adalah 30,0+20,8 ppm (rentang: 7,1- 78,3 ppm). Sementara itu, median iodium air minum adalah 650 μg/L (rentang: 50-1791 μg/L). Asupan iodium ibu menyusui dan bayinya, dari air minum, adalah sangat tinggi. Pada ibu menyusui ada risiko hipertiroidisme subklinik maupun hipertiroidisme. Sebaliknya, ada risiko hipotiroidisme pada bayi umur < 6 bulan. [Penel Gizi Makan 2013, 36(2):103-112]Kata kunci: kelebihan iodium, status iodium, ibu menyusui, bayi, garam, air